Governance and service quality in reorganised Jammu and Kashmir: A case of urban and rural consumers - Sharma, Alka Gupta, Anil and Mahajan, Honeyka (Nagarlok: Quarterly Journal of Urban Affairs)
The reorganisation of state of Jammu and Kashmir had prompted various noteworthy reforms aimed at ensuring good governance in the Union Territory. By employing the SERVQUAL Model, the study examines the quality of service delivery of the governance, post-reorganisation of the state from the citizens$1 (Bperspective. The data were gathered using cluster random sampling technique and a total of 578 usable responses were collected on-site via self-administered questionnaires from the respondents belonging to urban, semi-urban and rural areas of the selected districts of Jammu & Kashmir. The data were analysed by adopting structural equation modeling for which PLS-SEM 4 was used. Findings indicate that all dimensions of service quality (tangibility, participation, rule of law, responsiveness, accountability and trust in government) significantly impact citizens$1 (Bsatisfaction. Therefore, SERVQUAL is an effective tool for determining citizens$1 (Bsatisfaction. Theoretically, this study contributes to the literature of good governance by incorporating the recent reforms initiated in the UT of J&K. Practically, it allows the policymakers and government officials to improve their services and further enhance satisfaction among citizens.- Reproduceds
Keywords: Good governance, Reforms, Jammu and Kashmir, SERVQUAL model, Citizens